La symbolique poétique de Bachelard dans la musique d’avant-garde de Takemitsu - Kreidy, Ziad (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
The technique of the Japanese avant-garde composer Takemitsu is stimulated by extra-musical phenomena that have no obvious connection with sound. His creativity is closely tied to the contemplation of nature and is based on a metaphorical thinking that brings him closer to Bachelard’s writings on the poetic imagination. Takemitsu’s allegories of wind, water, air, dreams, the Japanese garden, circular temporality, and the positivity of silence are in line with Bachelard’s imaginative thought on water, dreams and the intuition of the moment. For both, the figurative archetype drawn from an element of nature exists only in its dynamic potential, which is infinite. The primary image is evolving and never limited to a fixed structure. It is the poetics of the ephemeral substance that prevails over the visibility of the general form. Thus, Takemitsu has synthesised the modern West and ancient Japan.